Preventive mechanisms of the degradation of the hybrid layer - Navarrete-Salgado, Jo´se Manuel (2023)
One of the biggest challenges in dentistry is to achieve a long-lasting and stable bond between restorative materials and dental tissues. The adhesive protocols have been changing over time to meet this objective, trying to maintain the integrity of the hybrid layer, so the factors that cause the degradation of the hybrid layer and the mechanisms proposed to prevent this degradation were reviewed. An investigation and compilation of specialized bibliographic information on the subject was carried out, in scientific search engines such as PubMed, Scielo, Redalyc, Medigraphic, Scopus, among others, as well as books. For the inclusion criteria, years of publication between 2002 and 2022 were considered, focused on research works related to the degradation of the resin-dentin bonding interface and mechanisms to prevent this degradation in the hybrid layer. The placementof CHX is used after the application of phosphoric acid and before the adhesive, it inhibits the proteolytic activity of matrix metalloproteinases (MMPs) and the degradation of collagen fibers, thus achieving a longer life of resin dental restorations.